RELEVANCE OF THE PRODUCTION OF SPECIAL SHOES FOR AGGRESSIVE ENVIRONMENTAL CONDITIONS - KOZLOVSKA, LIUDMYLA; POMARANSKYI, OLEH (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article conducts a theoretical analysis of the importance of ensuring safety and health for workers in industries with aggressive environments. Attention is drawn to various factors that may affect workers' health, and a comprehensive approach to risk management is recommended to ensure safety and comfort in the workplace. Special emphasis is placed on the use of specialized footwear to reduce the risks of injuries and illnesses. The need to conduct an analysis of potential hazards in the workplace for employees working in environments with an increased risk to human health is identified, in order to properly select materials and construction for manufacturing specialized industrial footwear. It is noted that hazardous factors in the workplace can vary from physical and chemical to psychosocial and sanitary-hygienic, posing threats to the health and safety of workers and potentially leading to injuries, illnesses, and psychological problems.The importance of ensuring the safety and health of workers is underscored, along with the necessity of understanding these factors and taking measures to manage them and minimize risks. In this context, the use of specialized footwear becomes extremely important for ensuring the safety of workers, protecting their feet from contact with aggressive substances, reducing the risk of injuries from faulty equipment, and providing comfort and a sense of security for workers in the workplace. It should be noted that through a comprehensive approach to risk management, safety and health in the workplace can be ensured. The prospects for further research in the field of ensuring safe working conditions in industries with aggressive environments are outlined, including studies on the effectiveness of using specialized footwear and the selection of materials and construction for manufacturing specialized industrial footwear.
Keywords: special footwear; aggressive environment; dangerous factors; working conditions; industry